2018
DOI: 10.3928/01484834-20180522-03
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Clinical Performance of Baccalaureate Nursing Majors: A Retrospective Audit

Abstract: Understanding factors that affect clinical performance may help early identification of students at risk and allow for supportive intervention during placement and subsequent program completion. [J Nurs Educ. 2018;57(6):333-338.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…There are also multiple factors not examined in this study that may affect clinical performance ( 24 , 40 ), including the students' learning preferences ( 41 ), personal qualities, age, and outside employment ( 4 ). In addition, the students' personal characteristics (e.g., gender, ethnicity) and qualities of academic and clinical examiners themselves (experience in assessing, site effects) can have an impact on clinical and academic performance ( 6 , 42 ). Clinical performance measured by grades cannot be always translated to clinical competency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also multiple factors not examined in this study that may affect clinical performance ( 24 , 40 ), including the students' learning preferences ( 41 ), personal qualities, age, and outside employment ( 4 ). In addition, the students' personal characteristics (e.g., gender, ethnicity) and qualities of academic and clinical examiners themselves (experience in assessing, site effects) can have an impact on clinical and academic performance ( 6 , 42 ). Clinical performance measured by grades cannot be always translated to clinical competency.…”
Section: Discussionmentioning
confidence: 99%
“…While academic outcomes for different entry pathways into a BN program have been studied, other influences, such as student background, have not been explored ( 5 ). To date, only one Australian study has examined factors such as grade point average (GPA) (the number signifying the median value of the accrued final course grades) and domestic or international status ( 6 ). Findings from that study concluded that international students, and those with a lower GPA, were more likely to demonstrate lower clinical performance ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A student’s performance on placement is formally evaluated by the educator using the relevant university’s evaluation tool (McAllister & Nagarajan, 2015 ). Whilst most students pass their placement, the rates of failure in allied health and nursing programs have been reported to range from 1 to 32% (American Occupational Therapy Association, 2018 ; Attrill et al, 2012 ; Brandon & Davies, 1979 ; Foote, 2015 ; Gutman et al, 1998 ; Johnston et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Placement educators are more likely to be supervising CALD students due to this growth in international and domestic CALD students. Health professional students who speak a language other than English at home have been found to have less academic and professional placement success than students who are from the majority population and speak only English (Attrill et al, 2016a;Johnston et al, 2018;Woolf et al, 2011). Difficulties on placement, in particular, have been attributed to the placement educators' and students' differences in culture, communication and previous experiences of learning (Brennan et al, 2013;Mikkonen, Elo, Tuomikoski, et al, 2016;Newton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%